Dynamic plasmonic nano-traps for single molecule surface-enhanced Raman scattering. Issue 30 (5th July 2017) - Zhang, Yuquan; Shen, Junfeng; Xie, Zhenwei; Dou, Xiujie; Min, Changjun; Lei, Ting; Liu, Jun; Zhu, Siwei; Yuan, Xiaocong
Abstract : Intense electric fields at the nanoscale are essential for single molecule surface-enhanced Raman scattering (SERS) detection. Abstract : Intense electric fields at the nanoscale are essential for single molecule surface-enhanced Raman scattering (SERS) detection. Such fields can be achieved in plasmonic nano-gaps between nanoparticles and metal films through hybridization of surface plasmons. The nano-gaps could be formed and dynamically controlled by using plasmonic tweezers; however, the aggregation of particles in the plasmonic field degrades each particle's enhancement and spoils the nanosized-spatial resolution. Here, dual-plasmonic tweezers are proposed and demonstrated to accurately control the number of nano-gaps and enhancement by tailoring a crater-shaped potential well in the nano-trap system. As the electric field in the nano-gap is intense, SERS spectral signatures of a single molecular level are probed simultaneously. These advantages point towards the implementation of enhanced Raman spectra, and broad applications in optical molecular detection.